Política de Atenção à Saúde do Servidor Público Federal: um estudo sobre a implantação do Subsistema de Atenção à Saúde do Servidor SIASS (2009-2013) - Araujo, Aline Paes de (2014)
This thesis aims to study the Politics of the Federal Public Service Health (PASS), runs through Subsystem Server Federal Assistance to Health (SIASS) established by Decree N º. 6,830 of April 29, 2009 . Understand and analyze its implementation from the year in which the legal framework of the institution occurred. Because it is a social category of workers differentiated, it was necessary to know the current quota and delimit the federal public service executive level as the target audience. The absence of a politics prior to this and the fact that the Brazilian State as regulator to set labor relations between workers and private institutions, and the role of employer, do not have their own regulations, were some of the questions that this study sought to answer. For both, were used: literature search and document primary and secondary sources: legislation , the SIASS site , bank official data and some informal contacts with key persons responsible for the implementation of PASS in Brazil and in the state of São Paulo . However, the main advances brought by the new politics was the unification of standards and set of procedures in relation to the question of the health of the public servant , in the various organs that make up the system of Federal Civilian Government (SIPEC) . It should be emphasized that the delay politics and legislation (2009), when compared to that of private sector workers, deployed since the thirties of the last century, through the Social Security and the Consolidation of Labor Laws (CLT). Another issue that draws attention to the implementation of this politics for federal civil servants to process, is that it was not accompanied by infrastructure, power and skilled labor and adequate, sufficient budget